A kelet-közép-európai területi fejlődés két komponenséről - Horváth, Gyula (Közép-Európai Közlemények, 2013)
Two questions will be discussed in the following paper, which, on the basis of the European Union’s regional policy document plans, are considered symptomatic in the declining competitiveness of Eastern and Central European spatial policy and will be listed among the key factors in the preparation for the new programming period. These are the following: the institutional balance point of spatial development and the inevitable factor of knowledge-based development, research and development. Before the examination of these factors of content, the declining competitiveness of regional policy will be discussed in European comparison. In the period of the preparation for the new Structural Policy, besides the objectives of supports, resources and mechanisms of structural instruments, the exploitation of the new driving forces of spatial development must also be taken into consideration. The former question is related to the representation of national interests in the EU, the latter task belongs to the domain of national sectoral policies and institutional structures. The modification of factors shaping spatial development necessitates the transformation of the system of objectives, instruments and institutions of regional policy. This also implies the enforcement of national interests.